LAMTOR2 (p14) Controls B Cell Differentiation by Orchestrating Endosomal BCR Trafficking - Łyszkiewicz, Marcin; Kotlarz, Daniel; Ziȩtara, Natalia; Brandes, Gudrun; Diestelhorst, Jana; Glage, Silke; Hobeika, Elias; Reth, Michael; Huber, Lukas A.; Krueger, Andreas; Klein, Christoph (Frontiers in Immunology, 2019)
B-cell development and function depend on stage-specific signaling through the B-cell antigen receptor (BCR). Signaling and intracellular trafficking of the BCR are connected, but the molecular mechanisms of this link are incompletely understood. Here, we investigated the role of the endosomal adaptor protein and member of the LAMTOR/Ragulator complex LAMTOR2 (p14) in B-cell development. Efficient conditional deletion of LAMTOR2 at the pre-B1 stage using mb1-Cre mice resulted in complete developmental arrest. Deletion of LAMTOR2 using Cd19-Cre mice permitted analysis of residual B cells at later developmental stages, revealing that LAMTOR2 was critical for the generation and activation of mature B lymphocytes. Loss of LAMTOR2 resulted in aberrant BCR signaling due to delayed receptor internalization and endosomal trafficking. In conclusion, we identify LAMTOR2 as critical regulator of BCR trafficking and signaling that is essential for early B-cell development in mice.